2015
DOI: 10.1159/000380823
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vascular Calcifications on Arteriovenous Fistula Survival in Hemodialysis Patients: A Five-Year Follow-Up

Abstract: Background/Aims: Vascular calcifications are frequently found among dialysis patients, and the calcification process may influence the patient's outcome. The aim of the present study was to determine the role that vascular calcifications may have on autologous arteriovenous fistula (AVF) survival. Methods: This study included 90 patients (49 males, mean age 62 ± 11) with a native AVF treated by chronic hemodialysis (HD) for more than one year. The overall vascular calcification scores ranged from 0-11 (Adragao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…For example, Lee et al [39] have documented the presence of vascular calcification in upper extremity vessels used to create new vascular access. Studies have found that preexistent vascular calcification is associated with worse survival of native AVF [40,41]. The preexistent vascular calcification may be less relevant in AVG compared to AVF.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lee et al [39] have documented the presence of vascular calcification in upper extremity vessels used to create new vascular access. Studies have found that preexistent vascular calcification is associated with worse survival of native AVF [40,41]. The preexistent vascular calcification may be less relevant in AVG compared to AVF.…”
Section: Discussionmentioning
confidence: 99%
“…Calcification severity in patients on hemodialysis with working AVFs as determined by radiology correlated with worse AVF patency in a 5-year follow-up study (49). In contrast, using histologic analysis, preexisting microcalcification in arteries used for AVF creation did not predict postoperative stenosis, AVF maturation, or primary unassisted patency (38,50).…”
Section: Vascular Calcification and Avf Outcomesmentioning
confidence: 91%
“…Patients with visibly calcified arteries on radiography had inferior primary and secondary patency at 4-year follow-up as well as inferior total survival at 2 years. Jankovic et al 45 found that the degree of arterial calcification is strongly associated with access failure, with increasing degrees of calcification correlated with greater probability of access failure. Masengu et al 21 used duplex ultrasound-derived volume flow as a substitute for arterial diameter in 152 patients undergoing access creation.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 99%